Bonded composite magnet with excellent heat resistance and preparation method thereof

By using the combination of (Nd,Y)-Fe-B system magnetic powder and other magnetic powders in bonded composite magnets, combined with Y element addition and table processing technology, the existing bonded permanent magnets have been solved, and the problems of low magnetic performance and poor temperature resistance in medium and high temperature applications have been achieved, and higher magnetic performance and heat resistance are achieved.

CN119811812APending Publication Date: 2025-04-11MIANYANG WEST MAGNETIC TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510104981.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-23
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing bonded permanent magnets have problems with low magnetic performance and poor temperature resistance in medium and high temperature application scenarios, which limits their wide application.

Method used

A bonded composite magnet is adopted, which consists of (Nd,Y)-Fe-B system magnetic powder, ferrite magnetic powder, Sm-Fe-N system magnetic powder, Sm-Co-based magnetic powder or Mn-Bi system magnetic powder, etc., and is obtained by adding an appropriate amount of Y element and adjusting the proportion of different magnetic powders, combined with the use of binder and curing agent, and obtaining bonded composite magnets with excellent heat resistance through molding and molding and table processing processes.

Benefits of technology

The magnetic properties and heat resistance of bonded composite magnets are significantly improved, the coercive force temperature coefficient is reduced, and the maximum magnetic energy product is improved, which broadens its use range in medium and high temperature applications.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a bonded composite magnet with excellent heat resistance and a preparation method thereof, and belongs to the technical field of magnetic materials, the bonded composite magnet is composed of a main body component and an auxiliary material component, the main body component comprises (Nd, Y)-Fe-B series magnetic powder, and the auxiliary material component comprises (Nd, Y)-Fe-B series magnetic powder and (Nd, Y)-Fe-B series magnetic powder. The magnetic material further comprises at least one of ferrite magnetic powder, Sm-Fe-N series magnetic powder, Sm-Co series magnetic powder and Mn-Bi series magnetic powder, and the auxiliary material comprises a binder and a curing agent. By adding different kinds of magnetic powder and utilizing excellent temperature resistance of different kinds of magnetic powder, the use temperature of the bonded magnet can be increased, and a heat-resistant coating is further obtained through a special surface treatment process, so that the use temperature of the bonded magnet is further increased, the application scene of the bonded magnet in medium and high temperature is widened, and the application range of the bonded magnet is widened. And more stringent application requirements are met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of magnetic materials, and in particular to a bonded composite magnet with excellent heat resistance and a preparation method thereof. Background Art

[0002] With the development of industrial modernization and technological advancement, permanent magnetic materials, as an indispensable branch in the field of materials, have gradually penetrated into various industries such as national defense and military industry, civil transportation, and 5G communication technology. According to different preparation processes, permanent magnetic materials can be divided into sintered permanent magnets and bonded permanent magnets. Although the magnetic properties of bonded permanent magnets are not as good as those of sintered permanent magnets, they have the advantages of good magnetic property consistency, high dimensional accuracy, and complex shapes. In recent years, they have been widely used in precision motors, portable electronic devices, automotive micromotors, magnetic sensors, etc.

[0003] Currently, isotropic NdFeB magnetic powder can be obtained by melt quenching. The maximum magnetic energy product of the prepared isotropic bonded NdFeB magnet does not exceed 12MGOe, and it has poor temperature stability (the coercive force temperature coefficient is about -0.5% / K). The low magnetic properties and poor temperature resistance limit the application of bonded magnets in medium and high temperature scenarios. In addition, the coercive force temperature coefficients of ferrite magnetic powder, Sm-Fe-N magnetic powder, Sm-Co magnetic powder, and Mn-Bi magnetic powder are better than NdFeB magnetic powder, but in the process of their separate preparation and production, either the magnetic properties of the magnets are low, or the price is relatively expensive, or they cannot be mass-produced. Summary of the invention

[0004] One of the objects of the present invention is to provide a bonded composite magnet with excellent heat resistance to solve the above-mentioned problems.

[0005] In order to achieve the above-mentioned purpose, the technical solution adopted by the present invention is as follows: a bonded composite magnet with excellent heat resistance, the bonded composite magnet is composed of a main component and an auxiliary component, wherein the main component includes (Nd, Y)-Fe-B magnetic powder, and also includes at least one of ferrite magnetic powder, Sm-Fe-N magnetic powder, Sm-Co magnetic powder, and Mn-Bi magnetic powder, and the auxiliary component is a binder and a curing agent.

[0006] As a preferred technical solution, the content of Y element in the (Nd, Y)-Fe-B magnetic powder accounts for 1 to 20 wt.% of the total amount of Y element and Nd element.

[0007] As a preferred technical solution, the total content of ferrite magnetic powder, Sm-Fe-N magnetic powder, Sm-Co magnetic powder, and Mn-Bi magnetic powder is 5-40wt.%, the content of binder and curing agent is 1-6 wt.%, and the balance is (Nd, Y)-Fe-B magnetic powder, totaling 100wt.%.

[0008] As a further preferred technical solution, the content of the Sm-Fe-N series magnetic powder is 20 wt.%, the content of Sm-Co is 20 wt.%, the content of the binder is 2.3 wt.%, the content of the curing agent is 0.1 wt.%, and the rest is (Nd, Y)-Fe-B series magnetic powder, totaling 100 (Nd, Y)-Fe-B series magnetic powder.

[0009] As a preferred technical solution, the particle size of the (Nd, Y)-Fe-B magnetic powder is 70 to 110 μm.

[0010] As a preferred technical solution, the ratio of the particle size D50 of the (Nd, Y)-Fe-B system magnetic powder to the particle size D50 of other component magnetic powders is between 1 and 100.

[0011] It should be noted that: because there are differences in the particle sizes of the raw materials themselves, the particle size here only represents the average particle size D50. The preferred particle size ratio is to allow the coarse powder and fine powder to fill the gaps between each other and increase the product density.

[0012] A second object of the present invention is to provide a method for preparing the above-mentioned bonded composite magnet with excellent heat resistance, comprising the following steps: The (Nd, Y)-Fe-B magnetic powder, ferrite magnetic powder and / or Sm-Fe-N magnetic powder and / or Sm-Co magnetic powder and / or Mn-Bi magnetic powder, a binder and a curing agent are mixed in proportion to prepare a mixed rubber powder; The mixed rubber powder is molded and solidified to finally obtain a bonded composite magnet blank.

[0013] As a preferred technical solution, the obtained bonded composite magnet blank is subjected to a surface treatment process to obtain a heat-resistant coating.

[0014] As a further preferred technical solution, the surface treatment process includes any one of electrophoresis, spraying, infiltration, and parylene.

[0015] As a further preferred technical solution, the heat-resistant coating is prepared by using at least one of epoxy resin, polyparaxylene, polytetrafluoroethylene, and organic impregnation liquid.

[0016] Compared with the prior art, the advantages of the present invention are: The present invention firstly improves the comprehensive magnetic properties of Nd-Fe-B by adding an appropriate amount of Y element: on the one hand, the addition of Y element enables the Nd-Fe-B alloy to have a positive coercive force temperature coefficient within a certain temperature range, and the substitution of Nd has a certain positive effect on the temperature coefficient, but excessive addition will reduce the comprehensive magnetic properties of the magnet; Then, on the basis of adding Y element Nd-Fe-B, adding appropriate amount of ferrite magnetic powder, Sm-Fe-N magnetic powder, Sm-Co magnetic powder, Mn-Bi magnetic powder can reduce the cost and improve the comprehensive magnetic properties of the magnet, such as magnetic properties and heat resistance (coercive force temperature coefficient); Further obtaining a heat-resistant coating through a single or multiple surface treatment processes can further improve the temperature resistance of the magnet, increase the operating temperature of the bonded magnet in practical applications, and broaden the use of the bonded magnet in medium and high temperature application scenarios. DETAILED DESCRIPTION

[0017] The present invention will be further described in detail below with reference to examples, but the present invention is not limited to the following examples.

[0018] It should be noted that the addition percentage of the Y element in the present invention, unless otherwise specified, refers to the mass percentage of the total amount of "Y+Nd", that is, the replacement percentage of the Nd element in the Nd-Fe-B magnetic powder. For example, Y accounts for 5wt.%, which means that 5wt.% of the Nd element is replaced by the Y element.

[0019] Example 1

[0020] By adding Y element in different proportions, different (Nd, Y)-Fe-B magnetic powders were obtained by rapid quenching (a method well known in the art, see "Zhou Shouzeng, "Super Permanent Magnets-", the same applies to the following embodiments), and then an acetone solution was added, and then 0.1% of KH570 coupling agent and 2.3% of bisphenol A epoxy resin binder were added, and the mixture was fully mixed and stirred. After the organic solvent was volatilized, a mixed rubber powder was prepared, and a bonded magnet was prepared by molding and curing. The coercive force temperature coefficient was tested and the results are shown in Table 1: Table 1 Properties of bonded magnets made by adding different proportions of Y element Y wt.% 0 2 5 20 30 Coercivity temperature coefficient % / K -0.45 -0.43 -0.41 -0.31 -0.22 Maximum magnetic energy product MGOe 13.2 13.4 13.5 11.2 10.3 It can be seen from Table 1 that when the addition amount of Y element is 5wt.%, both the coercive force temperature coefficient and the maximum magnetic energy product performance can be taken into account. Compared with not adding Y element, the coercive force temperature coefficient is reduced while the maximum magnetic energy product performance is improved, thereby achieving better results.

[0021] Example 2

[0022] The (Nd, Y)-Fe-B magnetic powder containing 5 wt.% of Y element was obtained by rapid quenching method, and was mechanically mixed with SmFeN magnetic powder at a mass ratio of 100:0, 80:20, 60:40, and 40:60, respectively. Then, an acetone solution was added, and then 0.1 wt.% of KH570 coupling agent and 2.3 wt.% of bisphenol A epoxy resin binder were added. The mixture was fully mixed and stirred, and the organic solvent was evaporated to make a mixed rubber powder. The mixed powder was molded and cured to prepare a bonded composite magnet with excellent heat resistance. The coercive force temperature coefficient was tested and the results are shown in Table 2 below: Table 2 Properties of bonded composite magnets made with different SmFeN addition ratios SmFeN wt.% 0 20 40 60 Coercivity temperature coefficient % / K -0.41 -0.39 -0.37 -0.36 Maximum magnetic energy product MGOe 13.5 14.1 12.9 11.1 It can be seen from Table 2 above that when the SmFeN addition ratio is 20wt.%, both the coercive force temperature coefficient and the maximum magnetic energy product performance can be taken into account, achieving better results.

[0023] Example 3

[0024] (Nd,Y)-Fe-B magnetic powder (Y element accounts for 5 wt.%) and ferrite magnetic powder are mechanically mixed at a mass ratio of 100:0, 95:5, 80:20, 60:40, 40:60, and then an acetone solution is added, and then 0.1 wt.% of KH570 coupling agent and 2.3 wt.% of bisphenol A epoxy resin binder are added, and the mixture is fully mixed and stirred. After the organic solvent is volatilized, a mixed rubber powder is prepared, and a bonded composite magnet with excellent heat resistance is prepared by molding and curing. The magnetic flux loss after aging at 120°C for 2h is shown in Table 3 below: Table 3 Properties of bonded composite magnets made with different ferrite addition ratios Ferrite wt.% 0 5 20 40 60 Coercivity temperature coefficient % / K -0.41 -0.41 -0.40 -0.39 -0.38 Maximum magnetic energy product MGOe 13.5 13.7 11.5 8.1 5.8 It can be seen from Table 3 above that when the ferrite addition ratio is 5wt.%, both the coercive force temperature coefficient and the maximum magnetic energy product performance can be taken into account, achieving better results.

[0025] Example 4

[0026] (Nd,Y)-Fe-B magnetic powder (Y element accounts for 5 wt.%), ferrite magnetic powder, and Sm-Co magnetic powder are mechanically mixed at a mass ratio of 100:0:0, 80:20:0, 80:10:10, 80:0:20, and 60:20:20, and then an acetone solution is added, and then 0.1 wt.% of KH570 coupling agent and 2.3 wt.% of bisphenol A epoxy resin binder are added, and the mixture is fully mixed and stirred. After the organic solvent is volatilized, a mixed rubber powder is prepared, and a bonded composite magnet with excellent heat resistance is prepared by molding and curing. The magnetic flux loss after aging at 120°C for 2h is shown in Table 4 below: Table 4 Properties of bonded composite magnets made with different ferrite and Sm-Co magnetic powder addition ratios Ferrite wt.% 0 20 10 0 20 Sm-Co magnetic powder wt.% 0 0 10 20 20 Coercivity temperature coefficient % / K -0.41 -0.40 -0.35 -0.28 -0.27 Maximum magnetic energy product MGOe 13.5 11.5 12.6 13.8 12.2 It can be seen from Table 4 above that when the ferrite addition ratio is 0wt.%, and the Sm-Co magnetic powder addition ratio is 20wt.%, both the coercive force temperature coefficient and the maximum magnetic energy product performance can be taken into account, and better results can be achieved.

[0027] Example 5

[0028] (Nd,Y)-Fe-B magnetic powder (Y element accounts for 5 wt.%), Sm-Fe-N magnetic powder, and Sm-Co magnetic powder are mechanically mixed at a mass ratio of 100:0:0, 80:20:0, 80:10:10, 80:0:20, 60:20:20, and 40:30:30, and then an acetone solution is added, and then 0.1 wt.% of KH570 coupling agent and 2.3 wt.% of bisphenol A epoxy resin binder are added, and the mixture is fully mixed and stirred. After the organic solvent is volatilized, a mixed rubber powder is prepared, and a bonded composite magnet with excellent heat resistance is prepared by molding and curing. The magnetic flux loss after aging at 120°C for 2h is shown in Table 5 below: Table 5 Properties of bonded composite magnets made with different addition ratios of Sm-Fe-N and Sm-Co magnetic powders Sm-Fe-N wt.% 0 20 10 0 20 30 Sm-Co wt.% 0 0 10 20 20 30 Coercivity temperature coefficient % / K -0.41 -0.39 -0.33 -0.28 -0.26 -0.20 Maximum magnetic energy product MGOe 13.5 14.1 14.0 13.8 13.9 13.1 It can be seen from Table 5 above that, based on the optimal addition amount of Example 4, further adding 20 wt.% of Sm-Fe-N can further reduce the temperature coefficient and achieve better results.

[0029] Example 6

[0030] (Nd,Y)-Fe-B magnetic powder (Y element accounts for 5 wt.%) is added to acetone solution, and then 0.1 wt.% of KH570 coupling agent and 2.3 wt.% of bisphenol A epoxy resin binder are added, and the mixture is fully mixed and stirred. After the organic solvent is volatilized, a mixed rubber powder is made, and a bonded composite magnet with excellent heat resistance is prepared by molding and curing. After electrophoresis (epoxy resin), spraying (polytetrafluoroethylene), and impregnation (acrylic ester organic impregnation liquid commonly used in this field), it should be noted that the above process is only to obtain the same coating thickness; after treatment, the crushing strength of the magnetic ring is tested at 80°C (the test method refers to GB / T31967.2-2015) as shown in Table 6 below: Table 6 Strength of (Nd,Y)-Fe-B magnetic powders with different surface treatment methods Surface treatment No table Electrophoresis Spraying Impregnation Strength / N 150 164 166 172 It can be seen from Table 6 that the infiltration treatment can achieve better results.

[0031] Example 7

[0032] (Nd,Y)-Fe-B magnetic powder (Y element accounts for 5 wt.%) is added to acetone solution, and then 0.1 wt.% of KH570 coupling agent and 2.3 wt.% of bisphenol A epoxy resin binder are added, and the mixture is fully mixed and stirred. After the organic solvent evaporates, a mixed rubber powder is made. The mixed powder is molded and cured to prepare a bonded composite magnet with excellent heat resistance. After electrophoresis (1μm) + spraying (polytetrafluoroethylene), the crushing strength of the magnetic ring is tested at 80°C as shown in Table 7 below: Table 7 Properties of (Nd,Y)-Fe-B magnetic powders with different coating thicknesses Coating thickness No coating 1μm 2μm 4μm Strength / N 150 163 166 170 It can be seen from Table 7 that when the coating thickness is 4 μm, the strength is better.

[0033] It should be noted that Example 6 and Example 7 reflect the heat resistance of the product by measuring the strength of the product at high temperature.

[0034] It can be seen from the above embodiments that by adding different proportions of ferrite powder, Sm-Fe-N magnetic powder, Sm-Co magnetic powder, and Mn-Bi magnetic powder, the coercive force temperature coefficient of the bonded composite magnet is significantly reduced, and when Sm-Fe-N magnetic powder and Sm-Co magnetic powder are added together within 40 wt.%, not only the temperature performance of the magnet is improved, but also the magnetic properties can be further improved, achieving a coupling effect of 1+1>2. Further, a heat-resistant coating is obtained by surface treatment processes such as electrophoresis, spraying, infiltration, and parylene, and the high-temperature mechanical strength of the bonded composite magnet is greatly improved, and the crushing strength can be increased by up to 14%. Therefore, by mixing a single or multiple magnetic powders with excellent temperature resistance, the comprehensive magnetic properties of the magnet, such as magnetic properties and heat resistance, can be improved. At the same time, a heat-resistant coating is obtained by a single or multiple surface treatment processes, which can further improve the temperature resistance of the magnet.

[0035] It is understandable that, for those skilled in the art, any equivalent replacement or change to the technical solution and inventive concept of the present invention should fall within the protection scope of the claims attached to the present invention.

Claims

1. A bonded composite magnet having excellent heat resistance, characterized in that: The bonded composite magnet is composed of a main component and an auxiliary component, wherein the main component includes (Nd, Y)-Fe-B magnetic powder, and also includes at least one of ferrite magnetic powder, Sm-Fe-N magnetic powder, Sm-Co magnetic powder, and Mn-Bi magnetic powder, and the auxiliary component is a binder and a curing agent.

2. The bonded composite magnet having excellent heat resistance according to claim 1, characterized in that: The content of Y element in the (Nd, Y)-Fe-B magnetic powder accounts for 1-20wt.% of the total amount of Y element and Nd element.

3. The bonded composite magnet having excellent heat resistance according to claim 1, characterized in that: The total content of the ferrite magnetic powder, Sm-Fe-N magnetic powder, Sm-Co magnetic powder and Mn-Bi magnetic powder is 5-40 wt.%, the content of the binder and the curing agent is 1-6 wt.%, and the balance is (Nd, Y)-Fe-B magnetic powder, totaling 100 wt.%.

4. The bonded composite magnet having excellent heat resistance according to claim 3, characterized in that: The content of the Sm-Fe-N series magnetic powder is 20 wt.%, the content of Sm-Co is 20 wt.%, the content of the binder is 2.3 wt.%, the content of the curing agent is 0.1 wt.%, and the rest is (Nd, Y)-Fe-B series magnetic powder, totaling 100 (Nd, Y)-Fe-B series magnetic powder.

5. The bonded composite magnet having excellent heat resistance according to claim 1, characterized in that: The particle size of the (Nd, Y)-Fe-B system magnetic powder is 70-110 μm.

6. The bonded composite magnet having excellent heat resistance according to claim 1, characterized in that: The ratio of the particle size D50 of the (Nd, Y)-Fe-B system magnetic powder to the particle size D50 of the other component magnetic powder is between 1 and 100.

7. The method for preparing a bonded composite magnet having excellent heat resistance according to any one of claims 1 to 6, characterized in that: The following steps are involved: The (Nd, Y)-Fe-B magnetic powder, ferrite magnetic powder and / or Sm-Fe-N magnetic powder and / or Sm-Co magnetic powder and / or Mn-Bi magnetic powder, a binder and a curing agent are mixed in proportion to prepare a mixed rubber powder; The mixed rubber powder is molded and solidified to finally obtain a bonded composite magnet blank.

8. The preparation method according to claim 7, characterized in that: The obtained bonded composite magnet blank is also subjected to a surface treatment process to obtain a heat-resistant coating.

9. The preparation method according to claim 8, characterized in that: The surface treatment process includes any one of electrophoresis, spraying, impregnation and parylene.

10. The preparation method according to claim 8, characterized in that: The heat-resistant coating is prepared from at least one of epoxy resin, polyparaxylene, polytetrafluoroethylene, and organic impregnation liquid.